PENGEMBANGAN E-MODUL MATEMATIKA BERBASIS PROBLEM BASED LEARNING UNTUK MEMECAHKAN MASALAH MATEMATIKA MATERI KECEPATAN DAN DEBIT DI SEKOLAH DASAR - Aizzatul Izzah; Dian Kusmaharti; Via Yustitia (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The lack of learning media innovation in the form of technology-integrated e-modules is the background of this research. In addition, the low conceptual understanding of solving math problems in elementary school students needs media renewal in the form of e-modules with a problem-based approach or Problem Based Learning. The objectives achieved in this study were (1) to describe the process of developing a mathematical E-Module based on speed and discharge Problem Based Learning material in Elementary Schools (2) to determine the feasibility of a Mathematical E-Module based on speed and discharge Problem Based Learning material in Elementary Schools. This research includes the type of research and development or Research and Development (R&D) with the 4D development model used in this research but is only limited to 3 stages namely Define, Design, Develop. The data collection method uses validation questionnaires and unstructured interviews. While the data analysis technique used by researchers is qualitative data analysis to describe the product development process and quantitative data to determine product feasibility. The results obtained from this study are in the form of problem-based learning-based mathematical e-module development products on material speed and discharge in elementary schools which go through three stages with the results of the due diligence product assessment by media expert validators, material experts, and linguists getting the category " Very Decent”.